Development of a device to measure adherence and pressure characteristics of positive expiratory pressure therapies used by adults with cystic fibrosis. (3rd October 2022) - Ward, Nathan; Ward, Bruce; Stiller, Kathy; Kenyon, Amanda; Holland, Anne E
ABSTRACT: Introduction: Positive expiratory pressure (PEP) and oscillating positive expiratory pressure (OscPEP) therapies are often used by people with cystic fibrosis (CF) to facilitate airway clearance. However, suboptimal adherence and poor technique may reduce their effectiveness. Objective: To develop a device (PEPtrac) to accurately measure and provide preliminary clinical data of adherence and technique characteristics when airway clearance is performed using PEP/OscPEP devices. Methods: This study comprised two distinct phases: 1) a benchtop validation study; and 2) clinical study. Benchtop study: Accuracy of PEPtrac was measured by comparing it to video analysis for five different PEP/OscPEP devices. Clinical study: Clinical data were then collected for 18 adults with CF using one of three PEP/OscPEP devices (PariPEP S®, Acapella DH® or Aerobika®) unsupervised. Results: There was 100% agreement between PEPtrac and video analysis data. Clinical data revealed significant variability in expiratory duration and pressure properties between the three PEP/OscPEP devices and between participants. For example, expiratory duration with PariPEP S® (mean [SD] = 4.8 [1.2] sec) was longer ( p < .001) than Acapella DH® (3.7 [0.8] sec) and Aerobika® (2.9 [1.1] sec) and Aerobika® had a higher oscillation amplitude than Acapella DH® (6.4 [1.7] vs 5.3 [1.5] cmH2 O, p < .001). Discussion: Accurate measurement of PEP/OscPEP adherence and technique using a device such as PEPtrac was possible. Further research is required to investigate the clinical importance of the variability in technique seen in our clinical data.